Factors influencing family planning acceptors' use of IUD contraception in the working area of Medan Amplas District - Abdullah, Armelia Adel; Kaban, Lenni Apriani; Novianti, Desi; Hidayat, Andri; Ongko, Nicholas Xavier; Rosar, Naufal; Marpaung, Hans Hotma Haposan; Siregar, Lisdawaty; Sherliana, Ferra; Lizar, Budi Septhian; Angkasa, Celvin (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Indonesia's high population growth rate is a big problem and needs serious handling from all parties of society and government The family planning movement is carried out to build a prosperous family in order to create optimal human resources. The family planning program is one of the most effective ways to improve family resilience, health, and safety of mothers, children, and women. Descriptive quantitative research, where this study aims to determine the factors that influence family planning acceptors on the use of IUD contraceptives in the Medan Amplas working area in 2024 using a cross-sectional design where the independent variable and the dependent variable are identified at the same time. The results of this study are There is an influence of education (P<0.05), mileage (P<0.05), knowledge (P<0.05), attitude (P,0.05), attitude (P<0.05), husband support (P<0.05), health worker support (P<0.05), The most dominant factor affecting the use of IUD contraceptives is the variable Husband support Exp (B) = 2.50 means that if there is husband's support for the use of IUD contraceptives then there are 2.5 times the mother wants to participate as an acceptor of IUD contraceptives. It is expected to Improve the Awareness Campaign Program by holding campaigns that target husbands and other family members, explaining the importance of their support in the use of contraceptives.